The Study of Learning Styles among Mechanical Engineering Students from Different Institutions in Malaysia - Koh, Yit Yan; Chua, Yaw Long (Elsevier Ltd., 2012)
Learning style is viewed as a method of education that is particular to personal study experiences to achieve the best learning results, which is some cases, the deep learning experiences. To date, researchers have recognized at least 21 components, where normal individuals would have 6 to 14 strongly preferred learning styles. The understanding of these learning styles will help the lecturers in their design of the delivery of lecture to suit students’ learning styles to achieve deep learning among students. This research aims to look into the differences in learning styles among Mechanical Engineering students from different institutions and levels. In accordance to this, this paper will report the analyses of the types of learning styles among engineering students.